Prester John of the Indies: an ancient source of European worldviews - Ramos, M. (IIT Gandhinagar Faculty Talk, 2014)
The millenariam letter of the so-called Prester John of the Indies appeared in Europe in the late 12th century. A mix of the Biblical apocalypse and of the Alexander romance, this letter was an important propaganda piece in the preparation for the second Crusade. This mythical Christian Indian sovereign offered an alliance with Western powers to conquer the Holy Land of Jerusalem. This idea, which was conceived in the context of the war between European Christianity and Islam, later served as the ideological lever for the so-called Iberian Discoveries in the 15th-16th centuries, which set the scene for the ideas of European dominance of the world in the 19th century. Prester John, initially placed in India, was later identified with the Mongol empire and finally with Christian Ethiopia or Abyssinia. To the Portuguese who had arrived in Goa and Diu, this connection was at first important in military-strategic terms, but later had mainly a religious tone, since Ethiopian Christians were Orthodox and the Jesuit missionaries felt their duty to convert them to Catholicism. This talk will deal with the complex history of the Prester John myth, the semantics of European medieval cosmography and how this mental framework influenced world history and specifically Europe's relations with India and Africa.